Co-utilization of corn stover hydrolysates and biodiesel-derived glycerol by Cryptococcus curvatus for lipid production. (November 2016) - Gong, Zhiwei; Zhou, Wenting; Shen, Hongwei; Zhao, Zongbao K.; Yang, Zhonghua; Yan, Jiabao; Zhao, Mi
Graphical abstract: Highlights: Glycerol was assimilated simultaneously with sugars by Cryptococcus curvatus . Synergistic effects of glycerol and sugars can accelerate lipid production. Co-use of corn stover hydrolysates and biodiesel-derived glycerol was described. The co-utilization strategy provides a novel solution to advance lipid production. Lipids had similar fatty acid compositional profiles to those of vegetable oils. Abstract: In the present study, synergistic effects were observed when glycerol was co-fermented with glucose and xylose for lipid production by the oleaginous yeast Cryptococcus curvatus . Glycerol was assimilated simultaneously with sugars at the beginning of the culture without adaption time. Furthermore, better lipid production results, i.e., lipid yield and lipid productivity of 18.0 g/100 g and 0.13 g/L/h, respectively, were achieved when cells were cultured in blends of corn stover hydrolysates and biodiesel-derived glycerol than those in the hydrolysates alone. The lipid samples had fatty acid compositional profiles similar to those of vegetable oils, suggesting their potential for biodiesel production. This co-utilization strategy provides an extremely simple solution to advance lipid production from both lignocelluloses and biodiesel-derived glycerol in one step.